2014
DOI: 10.3791/51381
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Staining of <em>Arabidopsis thaliana</em> Secondary Cell Wall Elements

Abstract: Arabidopsis thaliana is a model organism commonly used to understand and manipulate various cellular processes in plants, and it has been used extensively in the study of secondary cell wall formation. Secondary cell wall deposition occurs after the primary cell wall is laid down, a process carried out exclusively by specialized cells such as those forming vessel and fiber tissues. Most secondary cell walls are composed of cellulose (40-50%), hemicellulose (25-30%), and lignin (20-30%). Several mutations affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 20 publications
0
90
0
5
Order By: Relevance
“…S1). To check the cellular distribution of the lignin, we examined cross‐sections of inflorescence stems for lignin autofluorescence under UV light, and by Mäule staining, which yields a red coloration with S lignin (Pradhan Mitra & Loque, ) (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). To check the cellular distribution of the lignin, we examined cross‐sections of inflorescence stems for lignin autofluorescence under UV light, and by Mäule staining, which yields a red coloration with S lignin (Pradhan Mitra & Loque, ) (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Ten milligrams of AIRs extracted from stem tissue were subjected to lignin composition analysis using the thioacidolysis method as reported previously (Zhao et al ., ), and cellular localization of lignin was determined by Mäule staining of cross‐sections of inflorescence stems (Pradhan Mitra & Loque, ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, we examined if overexpression of GhMYB7 caused ectopic deposition of SCW cellulose in transgenic Arabidopsis. Calcofluor white, Congo red, and S4B were used to image the cellulose distribution in plant cell walls (An-derson et al, 2010;Pradhan et al, 2014). As shown in Figure 3M-R, histological staining of cellulose in stems of the transgenic lines revealed that ectopic deposition of cellulose occurred in GhMYB7 transgenic stem epidermal cells, whereas SCW thickening was not detected in stem epidermal cells of wild-type plants.…”
Section: Overexpression Of Ghmyb7 In Arabidopsis Causes Ectopic Deposmentioning
confidence: 99%
“…For lignin staining, sections were stained with either phloroglucinol HCl or Maule reagent as described previously (Pradhan et al, 2014). Positive results for phloroglucinol staining indicate the presence of guaiacyl-lignin, whereas those for Maule reagent staining indicate the presence of syringyl-lignin.…”
Section: Sectioning Of Stems and Roots For Microscopic Analysismentioning
confidence: 99%
“…Sunflower is described as normally susceptible to low temperatures and salinity, but with a relative tolerance to drought stress due to its highly explorative root system. However, available information on gene expression in response to abiotic stresses in sunflower is still limited to few works (Pradhan Mitra et al 2014; Vitha et al 1995)…”
Section: Introductionmentioning
confidence: 99%